2017
DOI: 10.1016/j.jalz.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The aged rhesus macaque manifests Braak stage III/IV Alzheimer's‐like pathology

Abstract: The aging rhesus macaque provides the long-sought animal model for exploring the etiology of late-onset Alzheimer's disease and for testing preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
178
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 95 publications
(194 citation statements)
references
References 51 publications
14
178
2
Order By: Relevance
“…When frequency data were collapsed across age and treatment groups, we found that pS214‐tau was highly enriched in the cytoplasm of both axon terminals and spines. Many cytoplasmic tau immunogold particles were associated with lipid‐rich endomembranous structures (e.g., the spine apparatus), closely mirroring recent observations by others (Carlyle et al, ; Paspalas et al, ). In spines, pS214‐tau reactivity was also prevalent in the synaptic domain.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…When frequency data were collapsed across age and treatment groups, we found that pS214‐tau was highly enriched in the cytoplasm of both axon terminals and spines. Many cytoplasmic tau immunogold particles were associated with lipid‐rich endomembranous structures (e.g., the spine apparatus), closely mirroring recent observations by others (Carlyle et al, ; Paspalas et al, ). In spines, pS214‐tau reactivity was also prevalent in the synaptic domain.…”
Section: Discussionsupporting
confidence: 84%
“…Similar to patterns of synaptic distributions of pS214‐tau observed by others, and favoring roles for tau in mediating interactions between N‐methyl‐D‐aspartate (NMDA) receptors and the PSD, and in feedforward calcium signaling, p‐tau was also relatively abundant within the synaptic and cytoplasmic domains of dendritic spines (Carlyle et al, ; Frandemiche et al, ; L. M. Ittner et al, ; Mondragon‐Rodriguez et al, ; Paspalas et al, ; Roberson et al, ; Salter & Kalia, ). In addition, it was often observed at the spine apparatus, as well as other endomembranous structures across the synaptic complex, consistent with earlier reports (Carlyle et al, ; Paspalas et al, ; data not shown). Dendritic spine subsynaptic and plasmalemmal bins each contained ~6% of p‐tau immunogold particles; the localization of tau within these domains supports its proposed interactions with multiple different signaling molecules, the actin cytoskeleton, and the lipid‐rich domains such as the plasma membrane (Y. Wang & Mandelkow, ).…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations